DIDACTIC CONDITIONS OF CREATIVE FORMATION ACTIVITIES OF FUTURE TEACHERS IN THE SYSTEM PERSONALLY ORIENTED LEARNING - O.S. Bilous (Academy of Cognitive and Natural Sciences, 2004)
The article exposes the didactic conditions according to which the process of forming students' creative activity in personal-oriented system of education at higher pedagogical school.